Analisis Pengendalian Kualitas Menggunakan Metode Lean Six Sigma Pada Part Arm Rear Break KYEA di PT Ciptaunggul Karya Abadi - Adinda Gita Azzahra; Dene Herwanto; Samitha Pujia Khan; Sekar Mustika Ayuningtyas; Wagiana Rohmah; Zaskya Indah Vindari (Fakultas Teknik, 2023)
PT Ciptaunggul Karya Abadi (CKA) is a manufacturer active in the country, and part arm rear break KYEA broken are one of the parts that are produced every month, and product defects occur frequently. Substantially companies need to improve the quality of products manufactured according to standards and prescribed specification in order to reduce product defect levels. This study aims to use lean six sigma DMAIC (Define, Measurem Analyze, Improve, and Control) approach and kaizen analysis to identify the factors that cause defect levels and suggest improvements to reduce the number of defect. The capacity of sigma obtained from the production process part arm rear break KYEA is 4,6. There are three types of defects in the production process, restice dented 9%, blank minus 27%, blunt serration 64%. In addition, kaizen analysis was performed by 5W+1H analysis. The results of this survey are expected to contribute to improving product qualitu, satisfaction customer, dan maximizing profits.